Application of Hyaluronic Acid as a Biopolymer Material in Reconstruction of Interdental Papilla in Rats - Zhang, Yiding; Zhang, Yifan; Wu, Hongkun; Hong, Guang (Frontiers in Materials, 2021)
Applying hyaluronic acid, a biopolymer material, in the treatment of interdental papilla reconstruction has become a trend. The main objective of this research is to investigate the histologic effect of hyaluronic acid on interdental papilla over time. Deficient interdental papilla models were surgically created in sixty-two Sprague-Dawley (SD) rats and were randomly treated with the injection of hyaluronic acid (HA group) or phosphate-buffered saline (sham control group) or left untreated (control group). After 2, 4, and 8 weeks, the rats were sacrificed in batches to observe the histological changes. A fluorochrome label was used to monitor bone formation in 8 weeks. Immunohistochemical analyses were performed to evaluate the expression of potentially relevant cytokines, vascular endothelial growth factor (VEGF), bone morphogenetic protein-2 (BMP-2), and Wnt-induced secreted protein 1 (WISP1) in the gingival tissue in 8 weeks. A preliminary study of HA degradation after 24 weeks was performed in two rats. Following the HA injection, no inflammation or granulomatous foreign body reaction was observed. HA was able to promote collagen fiber and alveolar bone regular formation in the reconstruction site. HA also enhanced VEGF, BMP-2, and WISP-1 expression in gingival tissue (p＜0.05). After 24 weeks, there was no HA filler observed in the interdental papilla. In conclusion, our study suggested that HA is an effective way to reconstruct deficient interdental papilla.